Determinants of stock market modern development: Evidence from Vietnam - Kim Quoc Trung, Nguyen (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
The paper estimates the macroeconomic variables affecting the stock price in Vietnam from 2009 to 2019. Based on the used autoregressive distributed lag (ARDL) model, the test shows a co-integration between stock prices and macroeconomic factors. The findings explore the optimal delay in the ARDL model as (1, 2, 1, 2, 0, 0, 2). Concretely, statistically significant evidence proves that the consumer price index, gross domestic product, interest rate, money supply, and oil price are the determinants of the stock price in Vietnam. In particular, the consumer price index and GDP have a direct relationship with the stock market, while interest rate, money supply, and oil price have opposite effects.